Performance characteristics of zinc oxide varistor processed under different pressing conditions - Karim, A.N. Mustafizul; Puyane, R.; El-Baradie, M.A; Hashmi, M. S. J. (1996)

(untitled)
Zinc oxide varistor blocks are commonly pressed by uniaxial double action compaction technique. There are a number of parameters which influence this processing operation and in this study two such compacting parameters - stress and speed were considered. Multiple discs were pressed under each condition to lake into account the statistical variation of the resultant effect Increasing the stress leads to enhanced packing of material making the green body more dense while the higher speed of compaction consolidates the powder quickly and the green compact ends up with more trapped air and gas. However, the effect of these pressing variables on sintered discs is not well established specially in terms of the eventual electrical performance. This analysis reveals that out of the two variables the influence of compacting pressure is more prominent. The speed of pressing also plays a significant role. Four important operating parameters of varistor were observed. These were the nominal voltage, clamp ratio. wattloss and energy absorption capability, A model has been developed to correlate the effects. Greater compacting pressure and speed are conducive to the clamp ratio but this condition leads to the undesirable increase in wattloss. Thus the fact that a favourable pressing condition for one parameter is found to be detrimental for another necessitates to make a compromise to set the optimum pressing conditions.